2010
DOI: 10.1299/jmmp.4.545
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Compact Unit for Wide Range Micro-Newton Force Measurement

Abstract: Wide range compact sensor is preferably sought for force sensing in testing of micro objects or local area of macro objects with the observation of high resolution microscope. This paper presents the design and development of an integrated passive cantilever type force sensing unit with the specificities of range variation, interchangeability of components and compact size by incorporating with cantilever, probe and a capacitive sensor for measurement of large range micro-newton forces in wide scope of applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…It was experimentally confirmed that the measurement uncertainty level of this type of force sensor was found within 0.4% of maximum load. The resolution of the present force sensor was about 10 nN [4].…”
Section: Microscope Systemmentioning
confidence: 89%
See 2 more Smart Citations
“…It was experimentally confirmed that the measurement uncertainty level of this type of force sensor was found within 0.4% of maximum load. The resolution of the present force sensor was about 10 nN [4].…”
Section: Microscope Systemmentioning
confidence: 89%
“…1(b). This compact, integrated force sensor has variable force range and can be used for obtaining force responses from various types of smallscaled objects [4]. The cross sectional area of the cantilever beam was 0.54 × 0.05 mm and the beam length was 29.5 mm.…”
Section: Microscope Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the testing apparatus are described elsewhere. 22) Table I. 23) Those values in Table I are the average values of the examined three Al wires.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum load for the force sensor was 670 mN, and it was experimentally confirmed that the measurement uncertainty of the sensor was less than 0.04% at the maximum load (o0.3 mN). Details of the force sensor are available in a previous paper (Akanda et al, 2010). The load-displacement curve was recorded for different loading directions (along the short or long axis in the elliptical crosssection of the hair) and at different loading positions (located 2 or 2.5 mm from the fixed end).…”
Section: Methodsmentioning
confidence: 99%